Ground Zero mosque in the context of America’s post-9/11 religious pluralism: CDA of mainstream news media’s coverage of the discursive event - Saad Boulahnane (IAIN Salatiga, 2018)
This article analyzes the Ground Zero Mosque discursive event and the discourses surrounding the American Muslim Community and explores the role of the media in the production and reproduction processes of anti-Muslim frames. To understand Islamophobia in the United States in the context of religious pluralism, this article adopts Critical Discourse Analysis, under which two theories unfold: sourcing theory and framing theory. The sourcing analysis targeted the media voices monitoring the discourses and contributing to the discursive construction and interpretation of mosque proposal into an agenda-led image. The second theory is framing, which consists of including a perceived reality—in the news—, making it more salient, and presenting it to the audience. The data analyzed were collected from CNN and Fox News via Lexis Nexis online academic database. A total of 225 media transcripts—(n=138) Fox News and (n=87) CNN—constituted the text and were coded and analyzed using Atlas.ti data mining software program. The critical analysis has resulted in a number of 180 voices—e.g. journalists, politicians, academics, officials, etc. — contribution of the discursive construction of the non-violence event, ofwhich 150 were anti-Muslim activists, journalists, politicians, reportedly formerMuslim Brotherhood member, etc. The study has also resulted in two mainframes: frame of illegitimacy and frame of terrorism, transforming the nonviolenceevent into a celebrated violent one, thereby providing a vivid image ofAmerica’s project of religious pluralism and its capacity to accommodate thereligions existing within the American confines.Artikel ini menganalisis peristiwa acara diskursif Masjid Ground Zero danwacana seputar Komunitas Muslim Amerika dan mengeksplorasi peran mediadalam proses produksi dan reproduksi bingkai anti-Muslim. Untuk memahamiIslamophobia di Amerika Serikat dalam konteks pluralisme agama, artikelini mengadopsi Analisis Wacana Kritis, di mana dua teori terungkap: teorisumber dan teori framing. Analisis sumber menargetkan suara-suara mediayang memonopoli wacana dan berkontribusi pada konstruksi diskursif daninterpretasi proposal masjid ke dalam pencitraan yang dipimpin oleh suatuagenda. Teori kedua adalah framing, yang terdiri dari memasukkan realitas yangdirasakan — dalam berita—, membuatnya lebih menonjol, dan menyajikannyakepada pemirsa. Data yang dianalisis dikumpulkan dari CNN dan Fox Newsmelalui database akademik online Lexis Nexis. Sebanyak 225 transkrip media—(n = 138) Fox News dan (n = 87) CNN — merupakan teks dan dikodekandan dianalisis menggunakan program perangkat lunak data mining Atlas.ti.Analisis kritis telah menghasilkan sejumlah 180 suara — misalnya wartawan,politisi, akademisi, pejabat, dll. - berkontribusi terhadap konstruksi diskursifdari peristiwa non-kekerasan, yang 150 di antaranya adalah aktivis anti-Muslim,jurnalis, politisi, mantan anggota Ikhwanul Muslimin, dll. Studi ini juga telahmenghasilkan dua kerangka utama: bingkai illegitimacy dan bingkai terorisme,yang mengubah peristiwa non-kekerasan menjadi peristiwa yang sangat kejam.Inilah gambaran yang jelas tentang proyek pluralisme agama Amerika dankapasitasnya untuk mengakomodasi agama-agama yang ada dalam batas-batasAmerika.